2016
DOI: 10.1007/s10103-016-2018-4
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of randomized controlled trial abstracts published in leading laser medicine journals: an assessment using the CONSORT for abstracts guidelines

Abstract: The objectives of this study were to assess the reporting quality of randomized controlled trial (RCT) abstracts published in leading laser medicine journals, and investigate the association between potential predictors and reporting quality. A total of 129 RCT abstracts were included and assessed. The mean OCS was 4.5 (standard deviation, 1.3). Only three quality items (interventions, objective, conclusions) were reported adequately in most abstracts (>80%). No abstract adequately reported results for the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…The results of this study showed that the quality of reporting in RCTs abstracts on drug therapy of periodontal disease was suboptimal. The inadequate reporting of abstracts was in line with previous studies on dentistry ( 10 - 12 ), as well as on other specialties ( 13 - 15 ). These results manifested a lack of adherence to the CONSORT guidelines for RCT abstracts.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of this study showed that the quality of reporting in RCTs abstracts on drug therapy of periodontal disease was suboptimal. The inadequate reporting of abstracts was in line with previous studies on dentistry ( 10 - 12 ), as well as on other specialties ( 13 - 15 ). These results manifested a lack of adherence to the CONSORT guidelines for RCT abstracts.…”
Section: Discussionsupporting
confidence: 77%
“…In terms of title, the deficient reporting of randomization may lead to irrelevant to database retrieval and omissions, leading to biases in systematic reviews. In the present study, 64.7% of abstracts titles could be identified as randomized, which was remarkably better than those of previous studies ( 13 , 16 ). In contrast, 13.2% of abstracts contained no information about “random”, neither in the title nor in the body of the abstract.…”
Section: Discussioncontrasting
confidence: 68%
“…Among previous studies that used the CONSORT for Abstracts checklist to assess RCT abstract reporting, five have taken into account the structure of abstracts as a confounding variable [ 24 28 ]. In four of these studies, structure was analysed in two categories (unstructured vs. structured): 3 studies found that the reporting quality was significantly higher in structured abstracts, but not significantly higher anymore when other explanatory variables were accounted for [ 24 26 ]; while in the other study, authors found no significant difference between structured and unstructured abstracts in univariable analysis [ 27 ]. In a more recent study, Bigna et al [ 28 ] categorised abstract structure into IMRaD, 8-heading and ‘one-block’.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, differences in results could also be attributed to different sources of abstracts. Our study included abstracts from recent issues of leading general medical/internal medicine journals, while those previous studies assessed abstracts from other medical specialty journals [ 26 , 27 ] or certain specific areas [ 24 , 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation